2002
DOI: 10.1021/ie0201011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Poly(aspartic acid) on the Removal Rates of Brushite Deposits from Stainless Steel Tubing in Turbulent Flow

Abstract: This research investigates the effect of poly(aspartic acid) (PASP) and its sodium salt on the removal of brushite (dicalcium phosphate dihydrate, DCPD) deposits from stainless steel tubing in turbulent flows. In the absence of PASP, DCPD removal is dominated by the abrasion of solid particles from the deposit by fluid shear and is influenced by the kinetics of the interfacial dissolution process. The presence of PASP promotes DCPD removal for pHs between 4 and 10, with an optimum enhancement at pH 5. A decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…The following additives were tested: Tween 20, polysorbate surfactant; TAC, ammonium citrate tribasic; EDTA, ethylenediaminetetraacetic acid (all provided by CTS S.r.l); PASP, sodium polyaspartate (Lanxess). All these additives are commonly used for these purposes except for PASP, which was selected as a possible "green" alternative to EDTA [35]. Agar gels with different concentrations and additives were tested with different application times: 15, 30, 60, 120 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…The following additives were tested: Tween 20, polysorbate surfactant; TAC, ammonium citrate tribasic; EDTA, ethylenediaminetetraacetic acid (all provided by CTS S.r.l); PASP, sodium polyaspartate (Lanxess). All these additives are commonly used for these purposes except for PASP, which was selected as a possible "green" alternative to EDTA [35]. Agar gels with different concentrations and additives were tested with different application times: 15, 30, 60, 120 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Investigators have tried to nd out effective and environmentally safe chelating agents to provide a feasible alternative to acid dissolution, which can cause corrosion in metallic process equipment and piping systems. 47 Previous studies demonstrate that PASP can promote the dissolution of calcium oxalate and calcium phosphate due to its ability to chelate metal ions in solution. [47][48][49] Therefore, the chelation of PASP with magnesium may also be a driving force for struvite dissolution.…”
Section: Effect Of Pasp Concentration On Struvite Dissolutionmentioning
confidence: 99%
“…47 Previous studies demonstrate that PASP can promote the dissolution of calcium oxalate and calcium phosphate due to its ability to chelate metal ions in solution. [47][48][49] Therefore, the chelation of PASP with magnesium may also be a driving force for struvite dissolution. Herein, the dependence of struvite dissolution on PASP concentration was examined at pH 8.…”
Section: Effect Of Pasp Concentration On Struvite Dissolutionmentioning
confidence: 99%
“…PASP is an effective calcium chelant and has been shown both to inhibit crystallization of calcium salts and to promote dissolution of calcium minerals under various conditions. A study done by our group investigated the effect of PASP on the dissolution of the calcium phosphate minerals DCPD (brushite) and HAP (hydroxyapatite)/DCPD under turbulent flow conditions. Dissolution was enhanced at alkaline pHs over a wide range of PASP concentrations and at low pHs from moderate to high PASP concentrations . It was concluded that PASP accelerates the rate of calcium phosphate removal via calcium sequestration during the interfacial dissolution step.…”
Section: Introductionmentioning
confidence: 95%
“…In recent years, a nontoxic, environmentally benign polymer, polyaspartic acid (PASP), has been identified as a possible “green” alternative to traditional calcium cleaning agents. , Donlar Corporation was awarded the 1996 Presidential Green Chemistry Challenge Award for developing environmentally safe thermal polyaspartate for use as a scale inhibitor for calcium carbonate, calcium sulfate, and barium sulfate . In a variety of tests, commercial polyaspartates of 3000−30 000 molecular weight met criteria for ready biodegradability, the most stringent measure of biodegradability .…”
Section: Introductionmentioning
confidence: 99%